“What is the moral of this story?”: morality, ethical reading and Islamic reading of Karim Raslan’s “neighbours” - Mohd Ramli, Aimillia; Moris, Megawati (Association of Malaysian Muslim Intellectuals, 2011)

(untitled)
Good literature, according to Plato, is one that promotes good morals for its readers. With the advent of theory, however, this notion has suffered a drawback since it was assumed that moral standards involved values deemed universal when they are, it seems, culturally dependent. This presents a dilemma to Muslim students of literature who have a tendency to look for moral values in literary works. Of particular concern are literary writings that discuss Islam from the perspective of morality as understood by Western Liberal Humanists. In addition, the issue of morality, in connection to literature, is once again becoming popular in literary studies with the advent of postmodern Levinisian concept of ethical reading. It emphasizes “alterity” that seeks to unearth the suppressed voice of “the Other” that defies the narrative voice of the text. Ethical reading, hence, presents individuality and diversity as irreducible to a singular scheme or totality. In using this approach and then critiquing it in favour of an Islamic approach to ethical reading, this essay will explore how Islam defines morality within the context of personal privacy and social responsibility, whether as Muslims and as a Muslim reader and author in the context of its rereading of Karim Raslan’s short story, “Neighbours” (1996).